Frescoes of St. Dimitrios Eleousis in Kastoria as an Example of Development of Local Conservative Stylistic Trends - Likhenko, Anastasia V. (Actual Problems of Theory and History of Art, 2023)
The Church of St. Demetrios Eleusis in Kastoria is a small one-nave 13th-century church that underwent extensive reconstruction in the 17th century. This monument is mostly known for its frescoes painted in 1609. However, in its eastern part, namely in a small apse and on the eastern wall, the murals of the first phase of the decoration of the church, attributed to the 1230s by Ioannis Sisiou, have been preserved. In the apse, there is a half-length image of the Mother of God with the Child and the Service of the Holy Bishops. In a small niche to the left, there is an image of St. Stephen. On the eastern wall, there is the scene of the Annunciation, traditionally divided into two parts by an apse, and, finally, in the upper register, there is a partially destroyed scene of the Ascension. As Sisiou rightly noted, such a choice of scenes is quite traditional for the 12th-century churches of Kastoria and its neighbors. The same program of murals in the eastern part is found in the Kastorian Agioi Anargyroi church, as well as in the Church of St. George in Kurbinovo. However, such overlaps between the murals of the Church of St. Demetrius and the programs of the most important monuments of the region from the previous Komnenian era are not the only conservative features of this ensemble. The stylistic features of these frescoes, in which two artistic styles can be clearly distinguished, allow the Church of St. Demetrios Eleusis to be regarded as one of the intermediate links between the local late Komnenian art and the emerging style of the 13th century, most vividly represented by the Church of the Ascension in Mileševo, the Basilica of Acheiropiitos in Thessaloniki, Churches of Sts. Peter and Paul in Tarnovo. They retain the tendency towards graphic character, a certain mannerism of poses and proportions, characteristic of the end of the 12th century, and the redundancy of draperies, obviously imitating the paintings of Kurbinovo. At the same time, the artists simultaneously use the techniques of three-dimensional modeling of faces, characteristic of the ensembles of the 1220s and 1230s, which would have been impossible in the 12th century. This organic coexistence of conservatism, an appeal to local tradition, and the emergence of new trends is very symptomatic of its time.This research was funded by the Russian Science Foundation (RSF), project no. 20-18-00294 “Artistic Traditions and Ecclesiastic-Political Ideology in the Medieval Architecture and Art of the Balkans. Macedonian question”.
Keywords: Byzantine art; monumental painting of northern Greece; Macedonian art; Kastoria